Analisis Amanat Tokoh Laut pada Novel Laut Bercerita Karya Leila S. Chudori - Nabila Syakir; Salsa Rachmania (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
This study aims to describe the character Laut in the novel Laut Bercerita by Leila S. Chudori and to convey the moral messages derived from Laut’s personality in the novel. This research employs a descriptive-analytic method with a literature study approach. The object of the research is the character Laut in the novel Laut Bercerita by Leila S. Chudori. The analysis reveals that Laut’s personality symbolizes the spirit of sacrifice and resistance to defend truth, courage, justice, and humanity. Laut’s personality convey profound messages and meanings about life, emphasizing that in navigating life, one should not prioritize ur uphold fear when moving forward, as long as truth remains the core principle to be fought for. This study potential to serve as a reference for future research.